Fazer ciência, fazer história: a sociologia da mudança social de Florestan Fernandes e de Costa Pinto - Souza, Patrícia Olsen de [UNESP] (2011)
This thesis discuss theoretical and interpretative approaches of Florestan Fernandes and L. A. Costa Pinto about social change in Brazil. These two sociologists actively participated in the intellectual debate about the development that happened in the 1950's and 1960's, decisive moment for the implantation of Brazil's capitalism, marked by project contests about the country's routes amid the rising linkage of civil society. In that context, distancing from the hegemonic nationalism in intellectual debate e from separate perspectives - close at a certain point, distant at others - Fernandes and Costa Pinto thought about the singularities of social change in underdeveloped countries, joining the debate of epistemological questions about the apropriate procedures that would allow sociology to contribute with the social change process on course, because these two authors understand the sociological knowledge simultaneously as History products and History producers. Fernandes' main problem was the process and the structural hurdles for the constitution of Brazil's civilization standard - based on democracy, on rationality and on the use of scientific knowledge for social planning. To face these questions, the author distilled a theoretical methodological and conceptual understructure from the sociological synthesis (in Mannheim's sense) of elements extracted from Durkheim,Marx and Weber tradition and, also, from the dialogue with North American sociology. By means of this procedure he identified the cultural delay as the main obstacle for the progress of class society in Brazil - in the 1950's. Amid Brazilian society's radicalisation in the early 1960's, the deepening of intellectual process about development, Fernandes was able to understand Brazil's social change standard as exclusivist, unilateral, formalist, irrational and antidemocratic because it is conducted by elites with limited mental horizons. Costa Pinto analysed social...